Converging forms: an examination of sub-Arctic, circumarctic, and Central Asian Ranunculus auricomus agg. populations - Bradican, John Paul; Tomasello, Salvatore; Vollmer, Judith; Hörandl, Elvira (Frontiers in Plant Science, 2024)
Phenotypic complexity in species complexes and recently radiated lineages has resulted in a diversity of forms that have historically been classified into separate taxa. Increasingly, with the proliferation of high-throughput sequencing methods, additional layers of complexity have been recognized, such as frequent hybridization and reticulation, which may call into question previous morphological groupings of closely related organisms. We investigated northern European, Asian and Beringian populations of Ranunculus auricomus agg. with phylogenomic analysis of 736 genes and 27,586 SNPs in order to deduce inter-relatedness and hybrid origin of this phenotypically and taxonomically complicated group from Europe characterized by a history of hybridization, polyploidy, apomixis and recent radiation. Ploidy levels and reproductive mode of northern European populations were assessed via flow cytometric seed screening. Additionally, in order to test phenotypic plasticity of dwarf forms previously described as species and summarized as R. monophyllus group we conducted climate chamber experiments under cold (northern) and warm (temperate) conditions. The northern European populations are tetra-to hexaploid and propagate primarily through apomixis. The complex is characterized by highly reticulate relationships. Genetic differentiation of the main clusters has occurred between the above-mentioned geographical regions. We find evidence for hybrid origin of taxa in these areas with differing genomic contributions from the geographically nearest European sexual progenitor species. Additionally, polyphyly in the taxa of the Ranunculus monophyllus group is supported. Experiments show low lability in traits associated with the Ranunculus monophyllus group. We conclude that multiple adaptations of hybrids to colder climates and shorter vegetation periods have shaped the phenotypes of the R. monophyllus group, and we suggest a formal classification as nothotaxa within the R. auricomus group.